Effect of alloying temperature on the capacitance–voltage and current–voltage characteristics of low‐pressure chemical vapor deposition SiNx/n‐GaN MIS structures. Issue 12 (9th September 2015) - Ma, Xiaohua; Liu, Ying; Wang, Xinhua; Huang, Sen; Gao, Zhu; Bao, Qilong; Liu, Xinyu
Abstract : The low‐pressure chemical vapor deposition (LPCVD)‐SiN x layer is deposited prior to the ohmic alloying as the passivation layer and gate dielectric layer in GaN device fabrication. The effect of alloying temperature on the LPCVD‐SiN x /GaN interface and LPCVD‐SiN x dielectric film is evaluated by the capacitance–voltage ( C – V ) and current–voltage ( I – V ) characteristics. The C – V analysis by frequency‐dependent method and Terman method shows that the higher density of interface states occurs at the higher alloying temperature, while I – V analysis indicates that the higher alloying temperature can lead to smaller current density with slightly deeper traps for Poole–Frenkel conduction. The hydrogen‐related bonds may be the cause and affects the interfacial properties of LPCVD‐SiN x /GaN as well as the electrical properties of LPCVD‐SiN x film.